Bone Marrow Chimeras to Study Neuroinflammation. (17th September 2018) - Laflamme, Nathalie; Préfontaine, Paul; Lampron, Antoine; Rivest, Serge
Abstract: Bone marrow transplantation is the standard of care for a host of diseases such as leukemia and multiple myeloma, as well as genetically inherited metabolic diseases affecting the central nervous system. In mouse models, bone marrow transplantation has proven a valuable tool for understanding the hematopoietic system and the homing of hematopoietic cells to their target organs. Many techniques have been developed to create chimeric mice, animals with a hematopoietic system derived from a genetic background that differs from the rest of the body. Current genetic tools allow for virtually limitless possibilities in the choice of donor mice. This protocol describes methods of bone marrow transplantation in mouse models for studies of the brain under basal and pathological conditions. Specific points to be addressed include the preparation of recipient mice by irradiation or chemotherapy; the choice, isolation, and injection of donor cells; and analytical methods such as fluorescence‐activated cell sorting and immunostaining. © 2018 by John Wiley & Sons, Inc.